Assessing and providing person-centred care of older people with cognitive impairment in acute settings: threats, variability, and challenges. Issue 1 (February 2019) - Grealish, Laurie; Simpson, Toni; Soltau, Dawn; Edvardsson, David
Abstract: Background: Person-centred care is widely accepted in health policy as a central focus for health services. However, research studies indicate that, for nurses, the person-centred care of older people with cognitive impairment is challenging. Aim: This study aimed to compare levels of person-centred care between wards and professional groups (ENs and RNs) providing tertiary hospital care of older people with cognitive impairment. Methods: A descriptive cross-sectional survey design, using the 15-item Person-centredness of Older People with cognitive impairment in Acute Care (POPAC) survey instrument, was undertaken. Results: Nurses working in hospital wards of a tertiary-level health service (n = 240; RR = 54.3%) responded. Person-centred care was rated lower in wards with higher patient turnover compared to wards with lower patient turnover. Person-centred care was rated higher by enrolled nurses compared to registered nurses. Discussion: Hospital context, specifically high turnover wards, present a threat to person-centred care, possibly related to the limited time available to undertake the personal care and associated conversations that can enhance nurses' knowledge of the person. ENs carry more responsibility for these tasks, possibly explaining the variability in person-centred scores between RNs and ENs. In comparison to other studies, nurses in this study had higher average scores for person-centred care, raising measurement as an important challenge in monitoring the implementation of person-centred care policy. Conclusion: The focus on health service efficiency appears to pose a threat to nurses' delivery of person-centred care. Further research into the variability between person-centred care of RNs and ENs, and investigation into the practices of other health disciplines would be valuable. Given the importance of person-centred care to the safety and quality of health services, the POPAC addresses the challenge of monitoring person-centred policy initiatives. However, self-report instruments should be balanced with other sources of information about practice.